THE STUDY OF MORPHOMETRIC AND DIVERSITY OF TURTLES IN AUR LAKE MUSI RAWAS REGENCY: Kajian Morfometrik dan Keanekaragaman Penyu di Danau Aur Kabupaten Musi Rawas - Widiya, Mareta; Dwi Riastuti, Reny; Febrianti, Yuli (Biospecies, 2022)
One of Indonesia extinct fauna which is still found in South Sumatra but less explored is reptile. Testudinata or chelonians are examples of turtles. Aur Lake has a lot of potential issues with various species, often finding them on the shores of Aur Lake. However, those turtles do not know yet what types of species. The high intensity of catching and decreasing environmental quality can also be a threat to the existence of turtles. This research is titled "The Study of Morphology and Diversity of the Turtles in Aur Lake Musi Rawas Regency. At the Aur Lake, Musirawas. The design of this study is descriptive qualitative with survey methods: Turtles were identified based on morphology, carapace, plastron, head, tail, feet and were identified there are 4 species and total 11 individuals comprising 5 of species Siebenrockiella crassicollis (Geomydidae), 1 Amyda cartilaginea (Trionichidae), 4 Cuora amboinensis (Geomydidae), and 1 Trachemys scripta (Emydidae). The diversity level (H') was obtained 1.162225545, and the evenness level was 0.838368515. The implication of this research was to provide information about the diversity of turtles around the Aur Lake stream in Musirawas Regency then strive to maintain the turtle's natural habitat in order to avoid the exploitation of animals and Aur Lake can be used as learning centers for student to study about biodiversity turtles and turtles conservation ex-situ and in-situ.